Integration of IoT on Power Monitoring and Control of Electrical Load for Home Automation System - Azman, Najwa Shahada; Abu Hassan, Omar (Progress in Engineering Application and Technology, 2021)
From the beginning of human history, a variety of technologies have been invented to make daily human life easier while preserving comfort, and virtually all technology has been developed requiring electric power. Getting the fan and lamp switched on all the time is a waste of energy and money if the user fails or lazy to switch it off, particularly when he/she is out of their home. Today's development of IoT (Internet of Things) technologies will help to solve this issue. This project presents the design and implementation of the Arduino Uno, Arduino Mega along with the ESP8266 Wi-Fi module and 5V relay which are based on the IoT concept. This system can be connected to the home electrical system so that the users can control and monitor the system by using their internet device anywhere and at any time via the Blynk platform. The system has also been equipped with sensors for control unit inputs so that users can control the switch in various ways, either online, by a sensor, or by a manual switch. ACS712 current sensors are used to allow users to monitor their electrical load power consumption at home. The construction of the prototype was carried out successfully based on the study and the designation that was made so that it can be observed how this system can operate. Current and power consumption data for each electrical load have been recorded and evaluated.